S B I (State Bank of India) - Probationary Officers' Recruitment Examination 2019 : Phase I & II - Solved Papers 2005 - 2018 (New Delhi C L Media, 2019)
2 mock Test (Phase I and II)
Includes 2 Mock Tests (Phase - I & II)
Keywords: Competitive Exams - Bank : India